Finding the Sweet Spot: A Study of Data Augmentation Intensity for Small-Scale Image Classification - Swastika, Windra (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
Finding the optimal level of data augmentation intensity remains one of the most challenging aspects of training deep learning models on small-scale datasets. While data augmentation is universally recognized as essential for preventing overfitting and improving generalization, excessive augmentation can paradoxically harm model performance by introducing too much variability in the training data. This research investigates the "sweet spot" of augmentation intensity through a comprehensive study of six distinct augmentation strategies on CIFAR-10, a representative small-scale image classification benchmark. We designed a controlled experiment comparing: No Augmentation (baseline), Basic torchvision transforms, Light Advanced albumentations, Moderate Advanced geometric-photometric combinations, Strong Advanced with noise injection and dropout, and AutoAugment Style with complex transformations. Our findings reveal a clear quadratic relationship between augmentation intensity and model performance (R² = 0.85), with peak performance achieved at moderate intensity levels (0.21 on our normalized scale). The Basic augmentation strategy wins with 79.04% validation accuracy, significantly outperforming both minimal augmentation (77.15%) and excessive augmentation (72.17%). Through statistical analysis including effect size calculations, confidence intervals, and correlation studies, we demonstrate that the "sweet spot" lies in balanced augmentation that provides regularization benefits without overwhelming the learning process. These findings offer evidence-based guidelines for practitioners working with small-scale image datasets.